Sport Tourism in the Republic of Uzbekistan and the Importance of National Sports and Their Prospects - Mavlonova Zulfina Ashraf qizi (Genius Publishing Group, 2022)
The importance of sports tourism and national sports in our country. This article discusses the efforts in the field of sport tourism, increasing the number of tourist bases as a result of increasing the number of mountain resorts, the development of the capacity of the National Olympic Committee, the Ministry of Tourism.
Keywords: sport; sport tourism; national sport; mountain resorts